Working Moms Interactions with their Children in Building Emotional Closeness - Salma Fadhilah; Farida Nurfalah; Novicky Alban Adiputra (Jurnal Parenting dan Anak, 2026)
This study was motivated by the increasing number of working moms who face challenges in maintaining emotional closeness with their children, particularly during the “golden age” from 0 to 5 years of age. Through this study, the author seeks to understand the nature of the interactions that take place, the factors that influence them, and the communication and time-management strategies employed by working moms in building emotional closeness with thei toddlers. To address these research questions, this study employed a qualitative method with a phenomenological approach. Five informants were interviewed in depth, supplemented by observations and documentation as supporting data, which were then analyzed using thematic analysis, the results indicate that emotional closeness between working moms and their children does not form instantly but rather through routine, dialogic, and effective interactions such as playing together, habing bedtime conversations, and expressing affection both verbally and nonverbally. The success in maintaining this closeness is influenced by three main factors: the mom’s ability to regulate her emotions, support from family, and the flexibility provided by the workplace. On the other hand, effective communication strategies also play a role, ranging from limiting distractions, making the most of transition times, to creating meaningful quality time. These findings ultimately confirm that what most determines emotional closeness is not how much time is spent with the child, but rather the quality of the interactions that take place. Therefore, family support and more adaptive workplace policies are essential for working moms to balance their dual roles effectively.